Application of Sterile Insect Technique (SIT) for Aedes albopictus (Skuse, 1895) in Sri Lanka: Dose optimization, mating competitiveness and release ratios - Jeevanie Harishchandra; Wimaladharma Abeyewickreme; Risintha Premaratne; Menaka Hapugoda (PLoS ONE, 2025)
Background Sri Lanka has experienced severe dengue epidemics in recent years, despite the extensive vector control measures taken. Therefore, it is necessary to find sustainable vector control strategies against dengue. Novel vector control tools need to be tested for the feasibility of applying them against local vectors. Sterile Insect Technique (SIT) is an increasingly popular vector control technique which has been adopted by many countries to suppress insect pest populations and is being tested for dengue vectors. Methods In this study, SIT was developed for Aedes albopictus (Skuse, 1895), one of the 2 dengue vectors present in Sri Lanka. The optimum radiation dose for sterilizing male pupae (age 24–48 hours) using a Co 60 source was determined based on the post-irradiation pupal and adult survival in males and induced sterility in females at different doses. Further, the effect of irradiation on mating competitiveness of the selected mosquito strain was assessed under laboratory and semi-field conditions. The optimum release ratio of irradiated males to wild males was assessed in laboratory and semi-field settings. Results The optimum radiation dose was 50 Gy among the series of doses (25, 30, 40, 50, 60, and 70 Gy) tested. When pupae were exposed to the optimal radiation dose, 100% pupal survival, 19-day median adult survival time and 99% induced sterility resulted. A 5:1 ratio of irradiated males to non-irradiated laboratory-reared or wild males in laboratory cages resulted in induced sterility of 75% and 62%, respectively. The respective values were 74% and 61% in large semi-field cages. Fried Competitiveness Index (FCI) of irradiated males against wild males of laboratory and wild origin were 0.63 and 0.43 in laboratory cages and 0.57 and 0.55 in large semi-field cages. Conclusion The males of Ae. albopictus irradiated at 50 Gy are adequately sterile and are competitive against the wild males. The release ratio of 5:1 irradiated males to wild males is a suitable ratio for the field application of SIT. The findings of the study will be important for the development of a protocol for future application of SIT for Ae. albopictus in Sri Lanka.